Different perspectives on teaching: of what teacher are we talking about? - Hatschbach Ourique, Maiane Liana; Pereira Ourique, João Luis (Revista Diálogo Educacional, 2014)
This work aims to reflect some images of teacher propagated in current discourses of education, focusing on the expectations and demands which corroborate to arrange different teaching figures. On the one hand, public policies use to their advantage a social imaginary of the profession to associate quality education to professional competence in teaching. Secondly, the different records of the Brazilian educational daily show the material misery and educational of the teacher work. From the tension between these two points, we ask about conceptions of rationality and formation that support the normative discourse of teaching. Still, can these models images-teacher effectively deal with the problems of the contemporary school? In light of the formative dimensions of Critical Theory, this study focuses on the writings of Theodor Adorno, performing a hermeneutic reading of space configured between the proposed and developed in the field of teaching.